A method for preparing concrete based on slag, silicon-aluminum compound and CO2 waste gas
By using ball mill grinding in slag concrete and combining silicon-aluminum compounds with CO2 exhaust gas, the problems of large dry shrinkage and low early strength of slag concrete are solved, efficient CO2 storage and environmental protection performance are achieved, and the concrete is improved and the ease and durability are improved. sex.
Patent Information
- Application Number
- CN202410047464.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-12
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-01-12
AI Technical Summary
The problems of existing slag concrete with large dry shrinkage and low early strength are difficult to effectively solve. At the same time, the efficiency of slag sequestration of carbon dioxide is insufficient and cannot meet the requirements of green and environmental protection.
The slag is mechanically ground by a ball mill, and silicon-aluminum compound and CO2 exhaust gas are added during the grinding process. The CO2 storage rate and early strength of the slag are improved through the carbonation reaction, and the porosity is increased to promote CO2 adsorption, forming carbonate and adsorption. CO2 to improve hydration activity.
It significantly improves the early strength and durability of slag concrete, reduces the loss of dry shrinkage slump, and achieves efficient CO2 storage and environmental protection performance.
Smart Images

Figure CN118005339B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method based on slag, silicon-aluminum compound and CO 2 The invention discloses a method for preparing concrete using waste gas, belonging to the technical field of green concrete. Background Art
[0002] Cement has many uses, the most important of which is as a cementitious material for concrete. Cement accounts for about 12% of the weight of concrete. The global annual consumption of cement is as high as billions of tons. Among the various types of cement, Portland cement is the most popular. However, the production of cement is a polluting activity, and carbon dioxide emissions during the cement production process account for about 5% of global carbon dioxide emissions. my country's cement production and consumption account for more than half of the world's total, and carbon dioxide emissions from the cement production process account for as much as 12% of the country's total emissions. About 77% of greenhouse gases in the air come from carbon dioxide, and the increase in carbon dioxide concentration is the core cause of global warming. Global warming is a key factor affecting the earth's social and ecological environment, and has caused problems such as rising sea levels and temperatures, ocean acidification, and reduced global ice thickness.
[0003] Slag is a kind of industrial solid waste with large output and low price. It does not release a large amount of carbon dioxide during the production process. Using slag to replace part of cement is an effective way to reduce carbon emissions in concrete production. However, in actual projects, problems such as large shrinkage and low early strength have occurred. Adding an activator can solve these problems. Sodium hydroxide and sodium silicate are commonly used slag activators and are also the most effective. However, these two activators are not naturally produced and require a lot of energy to produce. Sequestering carbon dioxide is also an important way to reduce the concentration of carbon dioxide. Carbon dioxide combines with minerals through carbonation reaction to achieve permanent sequestration. The carbonation product can play an activation role when the slag is hydrated. It is hoped that the carbonation product of slag can be used as a substitute for non-natural slag activators such as sodium hydroxide and sodium silicate. At present, there is a problem of small amount of carbon dioxide sequestration in slag carbon dioxide sequestration, and it cannot solve the problem of large shrinkage and low early strength of slag concrete. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a method based on slag, silicon-aluminum compounds and CO 2 The method of preparing concrete with waste gas, using the mechanical action of ball mill on slag and the addition of silicon-aluminum compounds to promote the slag to combine and adsorb CO 2 , increasing the CO 2 The sealing rate plays a significant role in activating the slag during hydration. During the ball milling process, part of the CO 2During ball milling, it dissolves in water to produce carbonate ions, and combines with active alkaline earth metal oxides in the slag to produce carbonates. The other part is adsorbed in the slag mixture and participates in the reaction during the concrete hydration process, which can improve the early strength of slag concrete and reduce the shrinkage slump loss of slag concrete. The prepared slag concrete has the characteristics of good workability, good durability and green environmental protection.
[0005] The present invention adopts the following technical solutions:
[0006] A novel method based on slag, silicon-aluminum compound and CO 2 The method for preparing concrete using waste gas comprises the following steps:
[0007] (1) Weigh a certain amount of slag, silicon-aluminum compound and distilled water, premix them in a blender, and put them into a ball mill using alumina as the ball milling medium;
[0008] (2) Use an air pump to introduce CO into the ball mill 2 Exhaust gas: when the gas pressure in the tank reaches the standard, turn off the air pump;
[0009] (3) Start the ball mill and grind at a rate of 400 to 600 rpm / min for 10 to 20 min. Then let it stand and repeat step (2) to continue grinding. Repeat this process several times until a specified mass M of CO is introduced. 2 The waste gas is completely reacted or adsorbed by the slag mixture. When the last CO 2 When the exhaust gas is not enough to make the gas pressure in the tank meet the standard, nitrogen is used to fill the tank until the gas pressure in the tank meets the standard. The industrial air cooler is used throughout the process to control the temperature of the ball mill tank at 20±2℃;
[0010] The inlet of the ball mill is equipped with an air inlet valve, which is connected to an air pump. The outlet is equipped with an air outlet valve and a pressure gauge. The air inlet valve and the air outlet valve are used to control the CO 2 The exhaust gas is introduced and discharged, and the pressure in the tank is monitored by a pressure gauge to determine the CO 2 Is it full and the reaction is complete? Pass CO 2 Before exhausting, nitrogen should be passed for 10 minutes to exhaust all the air in the tank.
[0011] (4) The median particle size of the mixture of slag and silicon-aluminum compound is determined by laser particle size analysis. If the median particle size does not meet the requirements, the mixture is further ball-milled in nitrogen until the slag and silicon-aluminum compound mixture that meets the requirements is obtained. The slag and silicon-aluminum compound mixture is combined with cement and coarse and fine aggregates to prepare slag concrete. During the grinding process: CO 2 A portion of it dissolves in water and reacts with calcium and magnesium ions in the mixture to produce carbonates, while the other portion is physically adsorbed between the pores of the slag mixture. The addition of silicon-aluminum compounds increases the porosity of the mixture, allowing it to absorb more CO. 2The mechanical action of the ball mill on the slag mixture can promote the adsorption of CO by the slag. 2 , increasing the adsorbed CO 2 Quality, improve the hydration activity of slag;
[0012] During grinding: CO 2 A part of it dissolves in water and reacts with calcium and magnesium ions in the slag mixture to produce carbonates, and the other part is physically adsorbed in the pores of the slag mixture. The addition of silicon-aluminum compounds increases the porosity of the mixture, allowing it to absorb more CO 2 The mechanical action of the ball mill on the slag mixture can promote the adsorption of CO by the slag. 2 , increasing the adsorbed CO 2 quality and improve the hydration activity of slag.
[0013] (5) mixing the mixture of slag and silicon-aluminum compound obtained in step (4) with silicate cement to obtain a slag cement mixture, adding water at a mass ratio of water to the slag cement mixture (0.35-0.41):1, and mixing with a certain mass of coarse and fine aggregates to prepare slag concrete;
[0014] The coarse aggregate is granite with a maximum particle size of 7-9 mm, the fine aggregate is natural sand, and the fineness modulus after mixing the coarse and fine aggregates is 4.0-4.5. During the hydration process of slag concrete, the CO adsorbed in step (3) 2 A beneficial carbonation reaction will occur, promoting hydration; the active silica and alumina in the silica-alumina compound react with the calcium hydroxide released by cement hydration to form stable calcium silicate hydrate (CSH) gel and hydrated calcium aluminate. Due to the consumption of calcium hydroxide, the hydration reaction of cement will be promoted.
[0015] (6) Pour the slag concrete obtained in step (5) into a mold, vibrate for 3 minutes to compact it, then seal the mold and cure it at a temperature of 22±2°C and a relative humidity of ≥90% for 24 hours, demould it, and cure it in a standard environment until the specified age.
[0016] The principle of the present invention is:
[0017] Slag, water and silicon-aluminum compounds in CO 2 Mechanical ball milling in the exhaust gas, part of CO 2 The calcium and magnesium dissolved in water react with the slag-silicon-aluminum mixture to form carbonates; part of the CO 2 The ball milling process will initially reduce the particle size of the slag mixture (i.e., a mixture of slag and silicon-aluminum compounds) until the median particle size reaches the required value. However, with further ball milling, the input energy will be converted into mechanical action to promote the adsorption of CO by the slag mixture. 2 .
[0018] CO 2 The calcium and magnesium dissolved in water react with the slag mixture to form carbonates, which can play a good filling and nucleation role and can also serve as an activator for the hydration of slag concrete. The carbonation reaction is roughly as follows: 2 In the waste gas environment, under normal temperature and high pressure, the active alkaline earth metal oxides (CaO, MgO) in the slag dissolve and hydrolyze in the water medium, releasing hydroxide ions, which increases the pH value of the mixture. The mixture exhibits strong alkalinity and has a strong ability to capture and seal CO. 2 Capacity; CO 2 It dissolves in water to form carbonic acid, which reacts rapidly with the hydroxide ions and calcium and magnesium ions in the mixture, causing the pH value of the mixture to begin to decrease and form carbonates. The reaction formula is as follows:
[0019] CaO+H 2 O=Ca(OH) 2
[0020] Ca(OH) 2 =Ca 2+ +2OH -
[0021]
[0022]
[0023]
[0024]
[0025] Ca 2+ +HCO 3 - =CaCO 3 +H +
[0026]
[0027] MgO+H 2 O=Mg(OH) 2
[0028] Mg(OH) 2 =Mg 2+ +2OH -
[0029]
[0030]
[0031]
[0032]
[0033] Mg 2+ +HCO 3 - =MgCO 3 +H +
[0034]
[0035] During the mechanical grinding process, when CO 2 After the reaction with the active alkaline earth metal oxides (CaO, MgO) in the slag mixture is complete, the surface of the mixture particles can still adsorb a portion of CO 2 , adsorbed CO 2 The quality is related to the porosity of the mixture. The particle size of kaolin is between 2μm and 10μm, and the particle shape is a curved and small tube, so the specific surface area is relatively large. The porosity is closely related to the specific surface area. The high porosity helps to better adsorb CO 2 . Fly ash particles are porous honeycomb structures with large specific surface area and high adsorption activity. The particle size range is 0.5 to 300 μm. It also has a porous structure with a porosity of more than 50%. In summary, since kaolin, fly ash and other silicon-aluminum compounds have large specific surface area, high porosity and high adsorption activity compared to slag, adding kaolin, fly ash and other silicon-aluminum compounds to slag can increase the porosity of the mixture and increase the adsorption of CO by the slag mixture. 2 quality.
[0036] During the hydration process of slag concrete, the adsorbed CO 2 It will react with other minerals except tetracalcium aluminoferrate (C4AF) to produce trigonal calcite and orthorhombic aragonite with extremely high thermal stability. 2 In the liquid phase, CSH and CaCO are generated. 3 As hydration progresses, CSH begins to react with CO 2 Reaction, decalcification to form amorphous silica gel SiO 2 ·nH 2 O fills the pores and improves the early strength of slag concrete. The specific reaction process is as follows:
[0037] 3(3CaO·SiO 2 )+(3-x)CO 2 +nH 2 O→xCaO·SiO 2 ·nH 2 O+(3-x)CaCO 3
[0038] 2(2CaO·SiO 2 )+(2-x)CO 2 +nH 2 O→xCaO·SiO 2 ·nH 2 O+(2-x)CaCO 3
[0039] xCaO·SiO 2 ·nH 2 O+xCO 2 →SiO 2 ·nH 2 O+xCaCO 3
[0040] The active silica and alumina in the silica-alumina compound react with the calcium hydroxide released by hydration to form stable calcium silicate hydrate (CSH) gel and hydrated calcium aluminate. The consumption of calcium hydroxide will further promote the hydration reaction. The carbonate produced by carbonation during the ball milling process prevents the conversion of ettringite into monosulfate (AFM) during the hydration process to stabilize ettringite (AFT). The molar volume of ettringite is greater than that of monosulfate, thus increasing the solid volume of the hydration product. At the same time, carbonate provides a nucleation site for the precipitation of hydration products, accelerates the hydration process, and improves the conversion rate of hydration. Since the carbonate itself has a fine particle size, it can fill the gaps between cement particles, making the cement particles densely packed, the pore structure refined, and the strength increased. The fine carbonate particles fill the gaps originally occupied by water, allowing more water to be used to lubricate the particles, reducing the slump loss and making the slag concrete workable.
[0041] Preferably, in the reaction, CO that forms carbonate with calcium and magnesium 2 The quality is mainly related to the quality of calcium oxide and magnesium oxide in slag and silicon-aluminum compounds, while the adsorbed CO 2 The quality is mainly related to the porosity of the slag after the silicon-aluminum compound is added. In step (1), when the mass of the slag is known, the mass of the silicon-aluminum compound added to the ball mill is calculated as follows:
[0042]
[0043] In the formula, m SA is the mass of silicon-aluminum compound; SSA SA , SSA S are the specific surface areas of silicon-aluminum compounds and slag, respectively (which can be obtained by low-temperature nitrogen adsorption test); ω is an empirical coefficient inferred from the influence of the porosity of silicon-aluminum compounds on the carbonization efficiency of slag, with a value range of 0.843-0.951; m S is the mass of slag; m Caois the mass of all calcium oxide in the mixture of slag and silicon-aluminum compounds; m Mgo It is the total mass of magnesium oxide in the mixture of slag and silicon-aluminum compounds.
[0044] The present invention can control the parameters such as the amount of silicon-aluminum compound, the pressure, time and temperature during ball milling to make the CO 2 With adsorbed CO 2 The mass ratio is about 4.0 to 2.5, so that the carbonate generated by grinding and the adsorbed CO 2 It can play the best activation role when slag and cement are hydrated.
[0045] Preferably, the ratio of the mass of distilled water added in step (1) to the total mass of slag silicon and aluminum compounds is 0.1:1.
[0046] Preferably, the silicon-aluminum compound is rich in SiO 2 With Al 2 O 3 Building materials, including but not limited to kaolin, fly ash and a mixture of the two.
[0047] Preferably, in step (2), when the pressure reaches 190-210 KPa, preferably 200 KPa, it is considered that the gas pressure in the tank meets the standard.
[0048] Preferably, in step (3), the ball mill is preferably milled at a rate of 500 rpm / min for 15 min and then allowed to stand for 10 min.
[0049] Preferably, in step (4), the median particle size of the mixture of slag and silicon-aluminum compound is 8.8-9.2 microns to meet the requirements.
[0050] When the carbonate particle size is larger than the slag mixture, the hydration product per unit volume of the slag concrete is reduced, showing a dilution effect, which will reduce the mechanical properties and durability of the slag concrete. In the process of ball milling, the present invention controls the grinding speed, pressure, temperature and time to make the carbonate fineness generated by carbonation at the nanometer level, and will not grow into carbonate with a particle size larger than the slag mixture, and will not have a negative impact on the particle size distribution of the slag mixture and the performance of the slag concrete.
[0051] Preferably, the CO introduced during ball milling is 2 The total mass of the slag is related to the content of calcium and magnesium oxides and the porosity of silicon and aluminum compounds. 2 When the slag mixture is carbonated, it will generate too much carbonate, which will reduce the average pore size of the slag mixture and weaken the ability of the slag mixture to absorb CO. 2 The ability of the slag to hydrate and the frost resistance of the slag concrete can be reduced.2 The total mass of the carbonation reaction is to ensure that the carbonation reaction produces an appropriate amount of carbonate, slag and a mixture of silicon-aluminum compounds required for the reaction and adsorption of CO 2 Total mass for:
[0052]
[0053] Where M Cao 、M Mgo and Represent the molar masses of calcium oxide, magnesium oxide and carbon dioxide respectively; μ is an empirical coefficient derived from the activity of alkaline earth metal oxides in the material, with a value range of 0.45-0.65; δ is a coefficient related to the porosity of the doped silicon-aluminum compound, with a value range of 1.1-1.4;
[0054] CO 2 Waste gas includes CO2 emitted by coal-fired power plants, steel production, etc. 2 One or more combinations of industrial waste gas, depending on the desired reaction and adsorption of CO in the mixture of slag and silicon-aluminum compounds 2 Total mass Use the following formula to calculate the mass M of the exhaust gas required to be introduced into the tank:
[0055]
[0056] M=∑m n K n
[0057] In the formula, x is CO 2 CO in exhaust gas 2 The mass of the industrial waste gas with the highest content; N represents CO 2 CO in exhaust gas 2 The highest content of CO in industrial waste gas 2 The proportion; xN / 1.112 represents the CO in CO2 waste gas 2 The highest content of CO in industrial waste gas 2 Quality; 1.112 is based on CO 2 CO in exhaust gas 2 The highest content of industrial waste gas contains CO 2 The empirical coefficient is derived from the amount of waste gas; M is the mass of the waste gas introduced into the tank, which is also the CO 2 The total mass of all industrial waste gases in the waste gas; 0.718 (Mx) is CO 2 Other industrial waste gas CO in waste gas 2 The sum of the contents, 0.718 is based on CO 2 Other industrial waste gas contains CO 2 Empirical coefficient derived from the sum of the quantity proportions; mn is the mass of each industrial waste gas, K n For each industrial waste gas CO 2 The proportion.
[0058] Since CO2 waste gas contains a variety of industrial waste gases, and the CO2 content in different types of industrial waste gases is different, the utilization efficiency during carbonization is also different. At the same time, the above formula can determine the quality of various industrial waste gases required.
[0059] Due to CO 2 The waste gas has different sources, and the proportion of each component in the chemical composition may sometimes vary greatly. The composition is complex, and this empirical coefficient has a correction effect to improve the formula for various types of CO 2 Suitability of exhaust gases.
[0060] The empirical coefficients 1.112 and 0.718 are based on the CO 2 The content data are fitted in the software and are representative because they are obtained from a large amount of data analysis.
[0061] Preferably, the ground slag mixture contains carbonates and CO adsorbed in the pores. 2 During the hydration process of the slag mixture and cement, the excess carbonate and CO 2 The hydration activity of slag and cement will not be increased. In order to achieve the best activation and hydration effect of the carbonized slag mixture, in step (5), the amount of silicate cement is determined according to the mass of the mixture of slag and silicon-aluminum compound:
[0062]
[0063] In the formula, m c is the required quality of Portland cement; M C represents the molar mass of carbonate produced by carbonization; 0.8 is the molar mass of CO in the carbonization reaction in the slag mixture 2 Quality and CO 2 The ratio of total mass; γ is a parameter related to the efficiency of carbonate activated cement, with a value of 2.72-4.27.
[0064] Preferably, the compressive strength of the prepared concrete is tested according to GB-T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". The CO2 sealed in the final slag mixture is calculated by acid elimination method. 2The acid digestion process is as follows: first, record the weight of an empty beaker with a glass rod, weigh about 40 grams of the slag mixture into the beaker, and put 300 milliliters of 10% nitric acid solution into another beaker and record its weight. Mix the weighed nitric acid solution with the slag mixture, stir with a glass rod for 10 minutes (until the bubbles disappear), and then record the weight of the mixture in the beaker. 2 The storage rate is calculated as follows:
[0065]
[0066] In the formula, m 1 is the weight of the slag mixture (about 40 g); m 2 is the weight of nitric acid solution (about 300 g); m 3 w is the weight of the mixture after continuous stirring for 10 minutes; f is the moisture content of the slag mixture.
[0067] CO 2 Indicates CO 2 The storage rate is multiplied by the weight of the slag mixture to obtain CO 2 Storage volume, CO 2 Storage amount = CO2 reacted 2 + Adsorbed CO 2 Mass, due to the loss of all reactions, is used to calculate or verify the required reaction and adsorbed CO obtained above 2 Total mass and reaction losses.
[0068] Preferably, the silicon-aluminum compound is metakaolin, and the mass parts of slag, metakaolin and distilled water are 27 parts, 3 parts and 3 parts respectively; the ball mill contains 50 parts of aluminum oxide;
[0069] When preparing slag concrete after ball milling, 35 parts of Portland cement, 23 parts of water, 99 parts of fine aggregate natural sand, and 147 parts of coarse aggregate granite are used.
[0070] Preferably, the silicon-aluminum compound is fly ash, and the slag, fly ash and distilled water are 29 parts, 18 parts and 4.7 parts by mass; and the aluminum oxide in the ball mill is 50 parts.
[0071] When slag concrete is prepared after ball milling, 39 parts of Portland cement, 31 parts of water, 140 parts of fine aggregate natural sand, and 200 parts of coarse aggregate granite.
[0072] Preferably, the silicon-aluminum compound comprises metakaolin and fly ash, with the ratio of metakaolin to fly ash being 1:1, and the slag, silicon-aluminum compound and distilled water being 31 parts, 5 parts and 3.6 parts respectively by mass; and the ball mill contains 50 parts of alumina.
[0073] When slag concrete is prepared after ball milling, 35 parts of Portland cement, 25 parts of water, 127 parts of fine aggregate natural sand, and 190 parts of coarse aggregate granite.
[0074] Preferably, the untreated slag concrete without adding silicon-aluminum compounds comprises slag and silicate cement, wherein the slag, silicate cement and water are 30 parts, 35 parts and 26 parts by mass, the fine aggregate is natural sand, and the coarse aggregate is granite. 110 parts.
[0075] The slag composition includes 38.47-41.78wt% CaO, 35.29-38.53wt% SiO 2 , 6.57~11.85wt%MgO, 8.17~11.41wt%Al 2 O 3 、0.20~0.67wt%Fe 2 O 3 , 0.18~0.56wt%K 2 O, 0.45~3.74wt% others.
[0076] The composition of metakaolin includes 43.84-49.7wt% SiO 2 、27.58~32.45wt%Al 2 O 3 、7.25~9.78wt%K 2 O, 0.74~2.02wt%Fe 2 O 3 , 7.29~15.47wt% others.
[0077] The fly ash composition includes 3.97-8.63wt% CaO, 45.20-48.34wt% SiO 2 、23.71~31.10wt%Al 2 O 3 、2.57~3.97wt%Na 2 O, 0.47-3.17wt% MgO, 4.45-24.42wt% others.
[0078] The present invention utilizes conventional slag grinding technology, uses high-porosity silicon-aluminum compounds such as metakaolin and fly ash as admixtures during ball milling, and introduces CO into the ball mill. 2 Exhaust gas to capture and store CO in the exhaust gas 2 , and utilize the beneficial carbonation reaction to promote the hydration of slag concrete. During the ball milling process, part of the CO 2The calcium and magnesium dissolved in water react with the slag mixture to form carbonates, which can play a good filling and nucleation role and can also serve as an activator for the hydration of slag concrete; part of CO 2 The admixture of silicon-aluminum compounds into the slag can increase the porosity of the mixture, and the mechanical action of ball milling can synergistically promote the adsorption of carbon dioxide by the mixture. 2 It will react with minerals other than tetracalcium aluminoferrate to form calcite and aragonite with high thermal stability; carbonates provide a nucleation site for hydration, accelerate the hydration process, and increase the hydration conversion rate. Carbonates fill the gaps between particles, making the particles densely packed, the pore structure refined, and the strength increased.
[0079] It is worth noting that the equipment used in the present invention, such as ball mill, air pump, pressure gauge, etc., can all be commercially available models, which will not affect the implementation of the present invention.
[0080] Where the present invention is not exhaustive, prior art may be used.
[0081] The beneficial effects of the present invention are:
[0082] 1. The present invention uses slag as a supplementary cementitious material for concrete, and silicon-aluminum compounds such as metakaolin and fly ash as modified admixtures for blast furnace slag. The raw materials used have the characteristics of low cost and large reserve. Silicon-aluminum compounds such as metakaolin and fly ash have larger specific surface area, higher porosity and adsorption activity than slag. Adding silicon-aluminum compounds to slag can increase the porosity of the mixture and increase the adsorption capacity of the mixture for CO 2 quality.
[0083] 2. The present invention uses a ball mill to reduce the particle size of slag and utilizes the mechanical action of the ball mill to capture CO in industrial waste gas. 2 , thus efficiently and conveniently completing the carbonation and CO removal of slag without adding conventional slag treatment steps. 2 adsorption.
[0084] 3. Slag concrete uses slag to replace part of the cement. Compared with ordinary concrete, it has the advantages of less cement usage and less carbon emissions, but it currently has problems such as low early strength and large shrinkage. The present invention adds silicon-aluminum compounds such as metakaolin and fly ash to the slag, and introduces CO during the ball milling process. 2 Waste gas can carbonate slag, which can promote the hydration of slag concrete, improve the hydration conversion rate, and increase the quality of hydration products, thereby improving the early strength of slag concrete and reducing the shrinkage slump loss of slag concrete, making the prepared slag concrete have the characteristics of good workability, good durability and green environmental protection.
[0085] 4. The present invention uses ball milling to remove CO2 Capturing CO from industrial waste gas 2 Using high-porosity silicon-aluminum compounds such as kaolin and fly ash as additives when ball-milling slag can improve CO 2 The conversion rate of CO 2 Sealed in slag concrete, industrial waste gas is utilized and CO in the atmosphere is reduced. 2 concentration, helping to mitigate the greenhouse effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0086] Figure 1 It is the principle flow chart of the present invention;
[0087] Figure 2 It is a schematic diagram of the ball mill structure;
[0088] In the figure, 1-ball mill, 2-air pump, 3-pressure gauge, 4-inlet valve, 5-outlet valve, 6-slag mixture, 7-temperature meter, 8-gas storage tank, 9-recovery tank, 10-gas transmission pipe, 11-exhaust pipe. DETAILED DESCRIPTION
[0089] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, they will be described in detail with reference to the accompanying drawings and specific embodiments, but are not limited to these. Anything not fully described in the present invention shall be based on conventional techniques in the art.
[0090] Example 1
[0091] A novel method based on slag, silicon-aluminum compound and CO 2 Method for preparing concrete using waste gas, such as Figure 1 , 2 As shown, the following steps are included:
[0092] (1) Weigh a certain amount of slag, silicon-aluminum compound and distilled water, premix them in a blender, and put them into a ball mill 1 with alumina as the ball milling medium; the silicon-aluminum compound is a compound rich in SiO 2 With Al 2 O 3 Building materials, including but not limited to kaolin, fly ash and a mixture of the two.
[0093] (2) Use the air pump 2 to introduce CO into the ball mill 1 2 Exhaust gas: when the gas pressure in the tank reaches the standard, turn off the air pump;
[0094] When the reading of the pressure gauge 3 reaches 200KPa, it is considered that the gas pressure in the tank meets the standard.
[0095] (3) Start the ball mill 1, grind at a rate of 400 to 600 rpm / min for 20 min, let it stand, repeat step (2) and continue grinding, repeat multiple times until a specified mass M of CO is introduced. 2 The waste gas is completely reacted or adsorbed by the slag mixture. When the last CO 2 When the exhaust gas is not enough to make the gas pressure in the tank meet the standard, nitrogen is used to fill the tank until the gas pressure in the tank meets the standard. The industrial air cooler is used throughout the process to control the temperature of the ball mill tank at 20±2℃;
[0096] like Figure 2 As shown, the feed port of the ball mill 1 is provided with an air inlet valve 4, which is connected to an air pump 2, and the discharge port is provided with an air outlet valve 5 and a pressure gauge 3. The air pump 2 is connected to an air storage tank 8 through an air delivery pipe 10, and the air storage tank 8 contains CO 2 The exhaust gas outlet valve 5 is connected to the recovery tank 9 through the exhaust pipe 11. The ball mill 1 contains the slag mixture 6. The ball mill is provided with a temperature detector 7. 2 The exhaust gas is introduced and discharged, and the pressure in the tank is monitored by the pressure gauge 3 to determine the CO 2 Is it full and the reaction is complete? 2 Before exhausting, nitrogen should be passed for 10 minutes to exhaust all the air in the tank.
[0097] (4) The median particle size of the mixture of slag and silicon-aluminum compound is determined by laser particle size analysis. If the median particle size does not meet the requirements, the mixture is further ball-milled in nitrogen until the slag and silicon-aluminum compound mixture that meets the requirements is obtained. The slag and silicon-aluminum compound mixture is combined with cement and coarse and fine aggregates to prepare slag concrete. During the grinding process: CO 2 A portion of it dissolves in water and reacts with calcium and magnesium ions in the mixture to produce carbonates, while the other portion is physically adsorbed between the pores of the slag mixture. The addition of silicon-aluminum compounds increases the porosity of the mixture, allowing it to absorb more CO. 2 The mechanical action of the ball mill on the slag mixture can promote the adsorption of CO by the slag. 2 , increasing the adsorbed CO 2 Quality, improve the hydration activity of slag;
[0098] During grinding: CO 2 A part of it dissolves in water and reacts with calcium and magnesium ions in the slag mixture to produce carbonates, and the other part is physically adsorbed in the pores of the slag mixture. The addition of silicon-aluminum compounds increases the porosity of the mixture, allowing it to absorb more CO 2 The mechanical action of the ball mill on the slag mixture can promote the adsorption of CO by the slag. 2 , increasing the adsorbed CO 2 quality and improve the hydration activity of slag.
[0099] (5) mixing the mixture of slag and silicon-aluminum compound obtained in step (4) with silicate cement to obtain a slag cement mixture, adding water at a mass ratio of water to the slag cement mixture (0.35-0.41):1, and mixing with a certain mass of coarse and fine aggregates to prepare slag concrete;
[0100] The coarse aggregate is granite with a maximum particle size of 7-9 mm, the fine aggregate is natural sand, and the fineness modulus after mixing the coarse and fine aggregates is 4.0-4.5. During the hydration process of slag concrete, the CO adsorbed in step (3) 2 A beneficial carbonation reaction will occur, promoting hydration; the active silica and alumina in the silica-alumina compound react with the calcium hydroxide released by cement hydration to form stable calcium silicate hydrate (CSH) gel and hydrated calcium aluminate. Due to the consumption of calcium hydroxide, the hydration reaction of cement will be promoted.
[0101] (6) Pour the slag concrete obtained in step (5) into a mold, vibrate for 3 minutes to compact it, then seal the mold and cure it at a temperature of 22±2°C and a relative humidity of ≥90% for 24 hours, demould it, and cure it in a standard environment until the specified age.
[0102] Example 2
[0103] A novel method based on slag, silicon-aluminum compound and CO 2 The method for preparing concrete with waste gas, as described in Example 1, in the reaction, CO which generates carbonate with calcium and magnesium 2 The quality is mainly related to the quality of calcium oxide and magnesium oxide in slag and silicon-aluminum compounds, while the adsorbed CO 2 The quality is mainly related to the porosity of the slag after the silicon-aluminum compound is added. In step (1), when the mass of the slag is known, the mass of the silicon-aluminum compound added to the ball mill is calculated as follows:
[0104]
[0105] In the formula, m SA is the mass of silicon-aluminum compound; SSA SA , SSA S are the specific surface areas of silicon-aluminum compounds and slag, respectively (which can be obtained by low-temperature nitrogen adsorption test); ω is an empirical coefficient inferred from the influence of the porosity of silicon-aluminum compounds on the carbonization efficiency of slag, with a value range of 0.843-0.951; m S is the mass of slag; m Cao is the mass of all calcium oxide in the mixture of slag and silicon-aluminum compounds; m Mgo It is the total mass of magnesium oxide in the mixture of slag and silicon-aluminum compounds.
[0106] The ratio of the mass of the distilled water added in step (1) to the total mass of the slag silicon and aluminum compounds is 0.1:1.
[0107] In step (4), the median particle size of the mixture of slag and silicon-aluminum compound is 8.8-9.2 microns to meet the requirements. When the carbonate particle size is larger than the slag mixture, the hydration product per unit volume of the slag concrete is reduced, showing a dilution effect, which will reduce the mechanical properties and durability of the slag concrete. In the process of ball milling, the present invention controls the grinding speed, pressure, temperature and time to make the carbonate fineness generated by carbonation at the nanometer level, and will not grow into a carbonate with a particle size larger than the slag mixture, and will not have a negative impact on the particle size distribution of the slag mixture and the performance of the slag concrete.
[0108] Example 3
[0109] A novel method based on slag, silicon-aluminum compound and CO 2 The method for preparing concrete from waste gas, as described in Example 2, can control the amount of silicon-aluminum compound, the pressure, time and temperature during ball milling, etc., so that the CO 2 With adsorbed CO 2 The mass ratio is about 4.0 to 2.5, so that the carbonate generated by grinding and the adsorbed CO 2 It can play the best activation role when slag and cement are hydrated.
[0110] Example 4
[0111] A novel method based on slag, silicon-aluminum compound and CO 2 The method for preparing concrete with waste gas, as described in Example 3, wherein the CO introduced during ball milling 2 The total mass of the slag is related to the content of calcium and magnesium oxides and the porosity of silicon and aluminum compounds. 2 When the slag mixture is carbonated, it will generate too much carbonate, which will reduce the average pore size of the slag mixture and weaken the ability of the slag mixture to absorb CO. 2 The ability of the slag to hydrate and the frost resistance of the slag concrete can be reduced. 2 The total mass of the carbonation reaction is to ensure that the carbonation reaction produces an appropriate amount of carbonate, slag and a mixture of silicon-aluminum compounds required for the reaction and adsorption of CO 2 Total mass for:
[0112]
[0113] Where M CaO 、M MgO and Represent the molar masses of calcium oxide, magnesium oxide and carbon dioxide respectively; μ is an empirical coefficient derived from the activity of alkaline earth metal oxides in the material, with a value range of 0.45-0.65; δ is a coefficient related to the porosity of the doped silicon-aluminum compound, with a value range of 1.1-1.4;
[0114] CO 2 Waste gas includes CO2 emitted by coal-fired power plants, steel production, etc. 2 One or more combinations of industrial waste gas, depending on the desired reaction and adsorption of CO in the mixture of slag and silicon-aluminum compounds 2 Total mass Use the following formula to calculate the mass M of the exhaust gas required to be introduced into the tank:
[0115]
[0116] M=∑m n K n
[0117] In the formula, x is CO 2 CO in exhaust gas 2 The mass of the industrial waste gas with the highest content; N represents CO 2 CO in exhaust gas 2 The highest content of CO in industrial waste gas 2 The proportion; xN / 1.112 represents the CO in CO2 waste gas 2 The highest content of CO in industrial waste gas 2 Quality; 1.112 is based on CO 2 CO in exhaust gas 2 The highest content of industrial waste gas contains CO 2 The empirical coefficient is derived from the amount of waste gas; M is the mass of the waste gas introduced into the tank, which is also the CO 2 The total mass of all industrial waste gases in the waste gas; 0.718 (Mx) is CO 2 Other industrial waste gas CO in waste gas 2 The sum of the contents, 0.718 is based on CO 2 Other industrial waste gas contains CO 2 Empirical coefficient derived from the sum of the quantity proportions; m n is the mass of each industrial waste gas, K n For each industrial waste gas CO 2 The proportion.
[0118] Since CO2 waste gas contains a variety of industrial waste gases, and the CO2 content in different types of industrial waste gases is different, the utilization efficiency during carbonization is also different. At the same time, the above formula can determine the quality of various industrial waste gases required.
[0119] Due to CO2 The waste gas has different sources, and the proportion of each component in the chemical composition may sometimes vary greatly. The composition is complex, and this empirical coefficient has a correction effect to improve the formula for various types of CO 2 Suitability of exhaust gases.
[0120] The empirical coefficients 1.112 and 0.718 are based on the CO 2 The content data are fitted in the software and are representative because they are obtained from a large amount of data analysis.
[0121] Preferably, the ground slag mixture contains carbonates and CO adsorbed in the pores. 2 During the hydration process of the slag mixture and cement, the excess carbonate and CO 2 The hydration activity of slag and cement will not be increased. In order to achieve the best activation and hydration effect of the carbonized slag mixture, in step (5), the amount of silicate cement is determined according to the mass of the mixture of slag and silicon-aluminum compound:
[0122]
[0123] In the formula, m c is the required quality of Portland cement; M C represents the molar mass of carbonate produced by carbonization; 0.8 is the molar mass of CO in the carbonization reaction in the slag mixture 2 Quality and CO 2 The ratio of total mass; γ is a parameter related to the efficiency of carbonate activated cement, with a value of 2.72-4.27.
[0124] Example 5
[0125] A novel method based on slag, silicon-aluminum compound and CO 2 The method for preparing concrete from waste gas is as described in Example 5, wherein the silicon-aluminum compound is metakaolin, and the mass parts of slag, metakaolin and distilled water are 27 parts, 3 parts and 3 parts respectively; and the ball mill contains 50 parts of aluminum oxide;
[0126] When preparing slag concrete after ball milling, 35 parts of Portland cement, 23 parts of water, 99 parts of fine aggregate natural sand, and 147 parts of coarse aggregate granite are used.
[0127] The slag composition includes 38.47-41.78wt% CaO, 35.29-38.53wt% SiO 2 , 6.57~11.85wt%MgO, 8.17~11.41wt%Al 2 O 3 、0.20~0.67wt%Fe 2 O 3 , 0.18~0.56wt%K2 O, 0.45~3.74wt% others.
[0128] The composition of metakaolin includes 43.84-49.7wt% SiO 2 、27.58~32.45wt%Al 2 O 3 、7.25~9.78wt%K 2 O, 0.74~2.02wt%Fe 2 O 3 , 7.29~15.47wt% others.
[0129] The fly ash composition includes 3.97-8.63wt% CaO, 45.20-48.34wt% SiO 2 、23.71~31.10wt%Al 2 O 3 、2.57~3.97wt%Na 2 O, 0.47-3.17wt% MgO, 4.45-24.42wt% others.
[0130] Example 6
[0131] A novel method based on slag, silicon-aluminum compound and CO 2 The method for preparing concrete with waste gas is as described in Example 6, wherein the silicon-aluminum compound is fly ash, and the slag, fly ash and distilled water are 29 parts, 18 parts and 4.7 parts by mass; and there is 50 parts of aluminum oxide in the ball mill.
[0132] When slag concrete is prepared after ball milling, 39 parts of Portland cement, 31 parts of water, 140 parts of fine aggregate natural sand, and 200 parts of coarse aggregate granite.
[0133] Example 7
[0134] A novel method based on slag, silicon-aluminum compound and CO 2 The method for preparing concrete with waste gas is as described in Example 6, wherein the silicon-aluminum compound includes metakaolin and fly ash, the ratio of metakaolin to fly ash is 1:1, the slag, the silicon-aluminum compound and distilled water are 31 parts, 5 parts and 3.6 parts respectively by mass; and there is 50 parts of alumina in the ball mill.
[0135] When slag concrete is prepared after ball milling, 35 parts of Portland cement, 25 parts of water, 127 parts of fine aggregate natural sand, and 190 parts of coarse aggregate granite.
[0136] Example 8
[0137] A novel method based on slag, silicon-aluminum compound and CO 2The method for preparing concrete with waste gas, as described in Example 6, wherein the untreated slag concrete without adding silicon-aluminum compounds comprises slag and silicate cement, wherein the slag, silicate cement and distilled water are 30 parts, 35 parts and 26 parts by mass, the fine aggregate is natural sand, and the coarse aggregate is granite. 110 parts.
[0138] The 3d and 7d compressive strength results of the prepared concrete tested in accordance with GB-T 50081-2019 “Standard for Test Methods for Physical and Mechanical Properties of Concrete” are shown in Table 1.
[0139] Table 1: 7d and 28d compressive strength of slag concrete
[0140]
[0141] Compared with the untreated slag-added concrete in Example 8, the 7d and 28d compressive strengths of the slag concrete prepared by the present invention are increased by about 11.9% and 16.3% on average.
[0142] The compressive strength of the prepared concrete was tested according to GB-T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". The CO2 stored in the final slag mixture was calculated using the acid elimination method. 2 The acid digestion process is as follows: first, record the weight of an empty beaker with a glass rod, weigh about 40 grams of the slag mixture into the beaker, and put 300 milliliters of 10% nitric acid solution into another beaker and record its weight. Mix the weighed nitric acid solution with the slag mixture, stir with a glass rod for 10 minutes (until the bubbles disappear), and then record the weight of the mixture in the beaker. 2 The storage rate is calculated as follows:
[0143]
[0144] In the formula, m 1 is the weight of the slag mixture (about 40 g); m 2 is the weight of nitric acid solution (about 300 g); m 3 w is the weight of the mixture after continuous stirring for 10 minutes; f is the moisture content of the slag mixture. The sealing rate is shown in Table 2:
[0145] Table 2: Slag concrete CO 2 Storage rate
[0146]
[0147] It can be seen that CO 2 The high storage rate makes industrial waste gas available for use, reducing CO 2concentration, helping to mitigate the greenhouse effect.
[0148] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing concrete based on slag, silicon-aluminum compounds and CO2 waste gas, characterized in that: The steps include: (1) Weigh a certain amount of slag, silicon-aluminum compound and distilled water, premix them in a blender, and put them into a ball mill using alumina as the ball milling medium; (2) Use an air pump to introduce CO2 waste gas into the ball mill tank, and turn off the air pump when the gas pressure in the tank reaches the standard; (3) Start the ball mill, grind at a rate of 400 to 600 rpm / min for 10 to 20 min, let it stand, repeat step (2) and continue grinding, repeat multiple times until a specified mass M of CO2 waste gas is introduced. When the last introduction of CO2 waste gas is insufficient to make the gas pressure in the tank meet the standard, nitrogen is used to fill the tank until the gas pressure in the tank meets the standard. An industrial air cooler is used throughout the process to control the temperature of the ball mill tank to 20±2°C; (4) Determine the median particle size of the mixture of slag and silicon-aluminum compound. If the median particle size does not meet the requirements, continue to ball mill in nitrogen until a mixture of slag and silicon-aluminum compound that meets the requirements is obtained; (5) mixing the mixture of slag and silicon-aluminum compound obtained in step (4) with silicate cement to obtain a slag cement mixture, adding water at a mass ratio of water to the slag cement mixture (0.35-0.41):1, and mixing with a certain mass of coarse and fine aggregates to prepare slag concrete; (6) pouring the slag concrete obtained in step (5) into a mold, vibrating it to compact it, and then sealing the mold and curing it at a temperature of 22±2° C. and a relative humidity of ≥90% for 24 hours, demolding it, and curing it to a specified age; In step (1), when the mass of the slag is known, the mass of the silicon-aluminum compound added to the ball mill is calculated as follows: In the formula, m SA is the mass of silicon-aluminum compound; SSA SA , SSA S are the specific surface areas of silicon-aluminum compounds and slag, respectively; ω is an empirical coefficient inferred from the influence of the porosity of silicon-aluminum compounds on the carbonization efficiency of slag, with a value range of 0.843-0.951; m S is the mass of slag; m CaO is the total mass of calcium oxide in the mixture of slag and silicon-aluminum compounds; m MgO It is the total mass of magnesium oxide in the mixture of slag and silicon-aluminum compounds.
2. The method for preparing concrete based on slag, silicon-aluminum compound and CO2 waste gas according to claim 1, characterized in that: The ratio of the mass of the distilled water added in step (1) to the total mass of the slag silicon and aluminum compounds is 0.1:
1.
3. The method for preparing concrete based on slag, silicon-aluminum compound and CO2 waste gas according to claim 2, characterized in that: The silicon-aluminum compound is a building material rich in SiO2 and Al2O3, including but not limited to metakaolin, fly ash and a mixture of the two.
4. The method for preparing concrete based on slag, silicon-aluminum compound and CO2 waste gas according to claim 3, characterized in that: In step (2), when the pressure reaches 190-210 kPa, the gas pressure in the tank is considered to meet the standard.
5. The method for preparing concrete based on slag, silicon-aluminum compound and CO2 waste gas according to claim 4, characterized in that: In step (3), the ball mill is ground at a speed of 500 rpm for 15 min and then allowed to stand for 10 min.
6. The method for preparing concrete based on slag, silicon-aluminum compound and CO2 waste gas according to claim 5, characterized in that: In step (4), the median particle size of the mixture of slag and silicon-aluminum compound is 8.8-9.2 microns to meet the requirements.
7. The method for preparing concrete based on slag, silicon-aluminum compound and CO2 waste gas according to claim 6, characterized in that: Total mass of CO2 required to react and adsorb in the mixture of slag and silicon-aluminum compounds for: Where M CaO 、M MgO and Represent the molar masses of calcium oxide, magnesium oxide and carbon dioxide respectively; μ is the empirical coefficient, ranging from 0.45 to 0.65; δ ranges from 1.1 to 1.4; CO2 waste gas includes one or more combinations of industrial waste gas containing CO2 emitted by coal-fired power plants and steel production, and the total mass of CO2 required to react and adsorb the mixture of slag and silicon-aluminum compounds. Use the following formula to calculate the mass M of the exhaust gas required to be introduced into the tank: M=∑m n K n In the formula, x is the mass of the industrial waste gas with the highest CO2 content in the CO2 waste gas; N is the proportion of CO2 in the industrial waste gas with the highest CO2 content in the CO2 waste gas; xN / 1.112 is the mass of CO2 in the industrial waste gas with the highest CO2 content in the CO2 waste gas; M is the mass of the waste gas introduced into the tank, which is also the total mass of all industrial waste gases in the CO2 waste gas; 0.718 (Mx) is the sum of the CO2 content of other industrial waste gases in the CO2 waste gas, m n is the mass of each industrial waste gas, K n It is the proportion of CO2 in each industrial waste gas.
8. The method for preparing concrete based on slag, silicon-aluminum compound and CO2 waste gas according to claim 7, characterized in that: In step (5), the amount of silicate cement is determined according to the mass of the mixture of slag and silicon-aluminum compound: In the formula, m c is the required quality of Portland cement; M C Indicates the molar mass of carbonate produced by carbonization; γ takes the value of 2.72-4.
27.
9. The method for preparing concrete based on slag, silicon-aluminum compound and CO2 waste gas according to claim 8, characterized in that: The silicon-aluminum compound is metakaolin, and the mass parts of slag, metakaolin and distilled water are 27 parts, 3 parts and 3 parts respectively; the ball mill contains 50 parts of aluminum oxide; When preparing slag concrete after ball milling, 35 parts of Portland cement, 23 parts of water, 99 parts of fine aggregate natural sand, and 147 parts of coarse aggregate granite are used.
